DESAIN PENGEMBANGAN SISTEM DISTRIBUSI DENGAN PEMBENTUKAN DISTRICT METER AREA (DMA) SPAM KOTA PURWAKARTA WILAYAH PELAYANAN KECAMATAN BUNGURSARI - Yusuf Tamher, Amir
The lack of access to piped drinking water in Purwakarta Regency has resulted in people's dependence on ground water or springs, which has the potential to accelerate extreme land subsidence. In an effort to increase access to piped clean water in Purwakarta Regency, which currently still reaches 12.07% service, the Purwakarta Regency Government built the Mulyamekar IPA to meet the clean water needs of the Purwakarta City SPAM which is specifically for the North Purwakarta area because it is still not served by piped clean water. The potential for increasing the amount of water production needs to be balanced with a reduction in the level of water loss which is currently 45%. For this reason, it is necessary to design a water distribution network to fulfill the 2024 RPJMN target of 30% piped clean water services with the establishment of a DMA (District Metered Area) to reduce the level of water loss in Purwakarta Regency to 25%. To achieve this goal, a quantitative analysis method is used, namely an approach in which the process of data collection, field observation, data analysis, and modeling is carried out with data certainty, calculations, and numbers. The planned distribution line design must meet several technical and non-technical criteria such as remaining pressure, speed and water quality, so that a distribution network is obtained that is able to meet the maximum needs of the service area in 2038 of 345.4 LPS divided into 11 DMAs. From the results of selecting alternatives using the SAW (Simple Additive Weighting) method, through various technical and non-technical parameters, alternative route 3 was selected as the best distribution route. Apart from that, based on financial aspects using the Net Present Value (NPV) and Benefit Cost Ratio (BCR) methods, designing the distribution network and establishing the Bungursari District DMA is economically feasible.